Helck. 2 - Nanao, Nanaki (Shōnen Sandē komikkusu., 2023)
"After the Demon Lord is slain at the hands of a lone human warrior, humans rejoice over the end of his reign of terror. But an intense tournament of powerful fighters hoping to be crowned the next Demon Lord has drawn in the unlikeliest of contestants--Helck, who claims to hate humans but is one himself! How will Helck change the course of the war between demons and humankind? Helck sets out with a group of demons led by the disguised Vermilio to defeat a mysterious group of winged soldiers and reclaim Castle Urum. However, before they can finish the fight, Helck and Vermilio are transported to a strange place. Now, the two must figure out how to survive in this new environment...and how to coexist!"--